2021
DOI: 10.1101/2021.07.21.453200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Variability of CRISPR-Cas Interference and Adaptation

Abstract: CRISPR-Cas defence is a combination of adaptation to new invaders by spacer acquisition, and interference by targeted nuclease activity. While these processes have been studied on a population level, the individual cellular variability has remained unknown. Here, using a microfluidic device combined with time-lapse microscopy, we monitor invader clearance in a population of Escherichia coli across multiple generations. We observed that CRISPR interference is fast with a narrow distribution of clearance times. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
(130 reference statements)
1
2
0
Order By: Relevance
“…They found that spacer acquisition occurs predominantly during the late exponential/early stationary phase. In line with this study, McKenzie et al (2) observed that the E. coli cells that adapted and cleared the target DNA earlier grew significantly slower than the population means. The soil-dwelling bacterium Pseudomonas aeruginosa can also infect the plant and human bodies.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…They found that spacer acquisition occurs predominantly during the late exponential/early stationary phase. In line with this study, McKenzie et al (2) observed that the E. coli cells that adapted and cleared the target DNA earlier grew significantly slower than the population means. The soil-dwelling bacterium Pseudomonas aeruginosa can also infect the plant and human bodies.…”
supporting
confidence: 81%
“…1 Correlation of spacer abundance with empirical MDT and optimal growth temperature. 2 Correlation of spacer abundance with predicted MDT and optimal growth temperature. MDT, minimal doubling time.…”
Section: Methodsmentioning
confidence: 99%
“…Brouns and coworkers take an important step to addressing this challenge by studying spacer acquisition and invader clearance at the single‐cell level (McKenzie et al , 2022). They focused on the type I‐E CRISPR‐Cas system in the bacterium Escherichia coli , which generally uses two modes of spacer acquisition called naive acquisition and primed acquisition (Fineran et al , 2014; Levy et al , 2015).…”
Section: Figure Single‐cell Tracking Of Invader Memorization By Crisp...mentioning
confidence: 99%